Fishing for sharks with bottom longline in Northern Brazil, duringthe years 1996 and 1997 - de Alencar, Carlos Alexandre Gomes; Santana, João Vicente Mendes; Oliveira, Glauber Gomes (Arquivos de Ciências do Mar, 2017)
The northern region of Brazil is endowed with an outstanding biomass of demersal fish resources, estimated as 250.000 ton/ year, of which 78.860 ton/year refer to the potential catch for sharks. Fishing is carried out with bottom longline, in depths between 15 and 70 meters, specially for bull shark, Carcharhinus leucas (Valenciennes, 1839), silky shark, C. falciformes, tiger shark, Galeocerdo cuvieri, and hammerhead shark, Sphirna spp. The main objectives of this paper are to describe the shark fishery and determine the abundance and fishing effort for C. leucas, based on logbooks of five trips totaling 117 days fishing spanning the period from Aprl, 1996 to March, 1997, in a region within the Marajoara Gulf bound by 05°N/02°S and 51°30’W/43°00’W. In that period 847 sharks were captured, amounting to 33.885 kg of carcass (without guts, fins and head), out of which 485 (57.4%) individuals were of C. leucas and the remaining 362 (42,6%) sorted out by the other species. A concentration of the fishing effort was observed in the second quarter, in depths between 21 and 60 meters, with a deployment northwards along the 50-meter isobath. The higher values of relative abundance were observed in the third and fourth quarters, when the flooding period occurs in the Amazon River basin, suggesting a seasonal migration of the bull shark in search of food, which is quite abundant in that period.